2013
DOI: 10.5125/jkaoms.2013.39.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates-related osteonecrosis of the jaw in Korea: a preliminary report

Abstract: ObjectivesBisphosphonates (BP) are widely used in medicine for inhibiting bone resorption; however bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a major side effect of BP. To date, there have been no specific reports on the incidence of BRONJ among Koreans. This study investigated the preliminary results from a nationwide survey of BRONJ in the Departments of Oral and Maxillofacial Surgery (OMFS) at individual training hospitals.Materials and MethodsA total of 15 OMFS departments (10 from dental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 23 publications
4
54
0
Order By: Relevance
“…Thus, measurement of BMD is can provide information for evaluating bone fracture risk [18,19]. The results in the present study showed that OVX reduced BMD in the right femurs and 4 th lumber vertebrae, which are rich in trabecular bone.…”
Section: Discussionmentioning
confidence: 50%
“…Thus, measurement of BMD is can provide information for evaluating bone fracture risk [18,19]. The results in the present study showed that OVX reduced BMD in the right femurs and 4 th lumber vertebrae, which are rich in trabecular bone.…”
Section: Discussionmentioning
confidence: 50%
“…Other medicines that stimulate bone formation (e.g., growth hormone, sodium uoride, and parathyroid hormone) or inhibit bone resorption (e.g., bisphosphonates and calcitonin) may prevent bone loss progression in established osteoporosis. However, these drugs are not effective for a large proportion of the world population, especially in developing countries, and their drugs have side effects, such as gastrointestinal reactions, cancers, osteonecrosis of the jaw, and reduced skeletal strength [13,14]. Consequently, to substitute or reduce the medicines used currently, there are efforts to develop new drugs with improved therapeutic efficacy, fewer undesirable side effects, and lower cost.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…However, these drugs are not effective for a large proportion of the world population, especially in developing countries. In addition, they have side effects such as gastrointestinal reactions, cancers, osteonecrosis of the jaw, and reduced skeletal strength [14,15]. Consequently, there are efforts to develop new drugs with improved therapeutic efficacies, fewer undesirable side effects, and lower costs, so as to substitute or reduce the usage of medicines currently in use.…”
Section: Introductionmentioning
confidence: 99%